Multi-Level Adaptive Corrections in Finite Dimensional Approximations (Journal of Computational Mathematics, 2018)
Based on the Boolean sum technique, we introduce and analyze in this paper a class of multi-level iterative corrections for finite dimensional approximations. This type of multi-level corrections is adaptive and can produce highly accurate approximations. For illustration, we present some old and new finite element correction schemes for an elliptic boundary value problem.
Keywords: Adaptive; Boolean sum; Correction; Finite dimensional; Multi-level.